Associations between nutritional energy delivery, bioimpedance spectroscopy and functional outcomes in survivors of critical illness. Issue 6 (29th April 2019) - Fetterplace, K.; Beach, L. J.; MacIsaac, C.; Presneill, J.; Edbrooke, L.; Parry, S. M.; Rechnitzer, T.; Curtis, R.; Berney, S.; Deane, A. M.; Denehy, L.
Abstract: Background: Patients who survive critical illness frequently develop muscle weakness that can impact on quality of life; nutrition is potentially a modifiable risk factor. The present study aimed to explore the associations between cumulative energy deficits (using indirect calorimetry and estimated requirements), nutritional and functional outcomes. Methods: A prospective single‐centre observational study of 60 intensive care unit (ICU) patients, who were mechanically ventilated for at least 48 h, was conducted. Cumulative energy deficit was determined from artificial nutrition delivery compared to targets. Measurements included: (i) at recruitment and ICU discharge, weight, fat‐free mass (bioimpedance spectroscopy) and malnutrition (Subjective Global Assessment score B/C); (ii) at awakening and ICU discharge, physical function (Physical Function in Intensive Care Test‐scored) and muscle strength (Medical Research Council sum‐score (MRC‐SS). ICU‐acquired weakness was defined as a MRC‐SS score of less than 48/60. Results: The median (interquartile range) cumulative energy deficit compared to the estimated targets up to ICU day 12 was 3648 (2514–5650) kcal. Adjusting for body mass index, age and severity of illness, cumulative energy deficit (per 1000 kcal) was independently associated with greater odds of ICU‐acquired weakness [odds ratio (OR) = 2.1, 95% confidence interval (CI) = 1.4–3.3, P  = 0.001] and malnutrition (OR = 1.9, 95% CI = 1.1–3.2, P  = 0.02). In similar multivariable linear models, cumulative energy deficit was associated with reductions in fat‐free mass (−1.3 kg; 95% CI = −2.4 to −0.2, P  = 0.02) and physical function scores (−0.6 points; 95% CI = −0.9 to −0.3, P  = 0.001). Conclusions: Cumulative energy deficit from artificial nutrition support was associated with reduced functional outcomes and greater loss of fat‐free mass in ventilated ICU patients.